2018
DOI: 10.1039/c8ra02168f
|View full text |Cite
|
Sign up to set email alerts
|

Nanolayer-like-shaped MgFe2O4 synthesised via a simple hydrothermal method and its catalytic effect on the hydrogen storage properties of MgH2

Abstract: In this study, the effect of nanolayer-like-shaped MgFe 2 O 4 that is synthesised via a simple hydrothermal method on the performance of MgH 2 for hydrogen storage is studied. ). X-ray diffraction spectra display the formation of new species which are Fe and MgO after dehydrogenation, and these new species are believed to act as the real catalyst that plays a crucial role in improving the sorption performance of the MgFe 2 O 4 -doped MgH 2 system by providing a synergetic catalytic effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(16 citation statements)
references
References 45 publications
(35 reference statements)
1
14
0
1
Order By: Relevance
“…. 针对纳米Mg基储氢材料, 朱敏等引入界面能对 van't Hoff公式进行修正, 得到如下公式: 表 1 常见轻质储氢材料及其理论储氢量 [18,19] 、金属合金 [20,21] 、氧 [35,36] . 通过掺杂, 材料形成了多相、多尺度的微结构 体系, 从而改善了材料的吸/放氢性能.…”
Section: 引言unclassified
“…. 针对纳米Mg基储氢材料, 朱敏等引入界面能对 van't Hoff公式进行修正, 得到如下公式: 表 1 常见轻质储氢材料及其理论储氢量 [18,19] 、金属合金 [20,21] 、氧 [35,36] . 通过掺杂, 材料形成了多相、多尺度的微结构 体系, 从而改善了材料的吸/放氢性能.…”
Section: 引言unclassified
“…10,11 Since the 1990s, enormous efforts have been dedicated for improving the hydrogenation/dehydrogenation behaviors of MgH 2 , using pure metal catalysts, 12,13 intermetallic compounds, 14 metal oxides, 15,16 carbides 17 and different families of composite and nanocomposite materials. [18][19][20][21] Recently, Shinde et al 22 demonstrated that successful self-assembly of MgH 2 nanoparticles in activated carbon led to the improvement of the physical and chemical behavior of the hydride phase for achieving reversible hydrogen storage.…”
Section: Introductionmentioning
confidence: 99%
“…Table S1 † summarizes the hydrogen storage properties of MgH 2 upon doping with selected metallic catalytic systems. [30][31][32][33][34][35] The present study has been conducted to investigate the possibility of improving the hydrogen storage behavior of nanocrystalline MgH 2 powders upon doping and reactive ball milling (RBM) with different molecular fractions (2.5, 5, and 10 wt%) of metallic glassy (MG) Zr 2 Ni nanopowders (used here for the rst time). More importantly, we have attempted to employ this new nanocomposite system for running an electric golf-cart, using a 1000 W proton-exchange membrane fuel cell (PEM-FC).…”
Section: Introductionmentioning
confidence: 99%